The Search for Predictability: A City Manager’s Perspective on Intergovernmental Relations - Stevens, Thomas (Maine Policy Review, 1995)
Thomas Stevens’ perspective on intergovernmental relations has been shaped particularly by his experience as town manager in Limestone, Maineas he watched the federal government attempt to close Loring Air Force Base on numerous occasions. The closing of Loring was an especially traumatic experience for central Aroostook County. Not surprisingly, the nature of intergovernmental relations and the economic future of the region are high on Tom Stevens’ list of concerns. In a recent interview with Maine Policy Review, he argued for a new partnership among the three levels of government that would be characterized by stability and predictability.